Las universidades públicas autónomas mexicanas: licenciaturas en ingeniería y su relación con el fomento académico de ser emprendedor (2016)
Inside the school activity at a higher level degree in engineering have often attended as a second option, due to the difficulty of take that. One way to encourage greater participation of students is to promote within these races the creation of the new company. Therefore, the overall objective of this research is to analyze within the curricula of state public universities. What they have degrees in engineering materials for the development of new businesses. It was found that in general terms there is very little involvement of entrepreneurial subjects in engineering with 6% of entrepreneurial subjects of all that you must take. Public universities have 75 variants of degrees in engineering. 80 % have plans with less than three entrepreneurial subjects and 14 of them do not have any entrepreneurial subject.